2011
DOI: 10.1124/jpet.111.184127
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Neuroprotective Effects of Biphalin, an Opioid Receptor Agonist, in a Model of Focal Brain Ischemia

Abstract: Approximately 795,000 people experience a new or recurrent stroke in the United States annually. The purpose of this study was to assess the protective effect of a nonselective opioid receptor agonist, biphalin, in brain edema and infarct damage by using both in vitro and in vivo models of stroke. In an in vivo model of ischemia, biphalin significantly decreased edema (66.6 and 58.3%) and infarct (52.2 and 56.4%) ratios in mouse transient (60-min occlusion/24-h reperfusion) and permanent (6 h) middle cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 39 publications
2
39
0
Order By: Relevance
“…In an in vivo model of ischemia, biphalin significantly decreased edema and infarct ratios in mouse transient and permanent middle cerebral artery occlusion models. Biphalin administration also decreased neurodegeneration in hippocampal, cortical, and striatal brain tissue after ischemia [9]. In vitro studies in hippocampal organotypic cultures demonstrated that biphalin possesses a much higher neuroprotective effect than morphine.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In an in vivo model of ischemia, biphalin significantly decreased edema and infarct ratios in mouse transient and permanent middle cerebral artery occlusion models. Biphalin administration also decreased neurodegeneration in hippocampal, cortical, and striatal brain tissue after ischemia [9]. In vitro studies in hippocampal organotypic cultures demonstrated that biphalin possesses a much higher neuroprotective effect than morphine.…”
Section: Resultsmentioning
confidence: 98%
“…However, it should be considered that these "non-specific" distributions and interactions may have a biological function; furthermore, these activities may be physiologically important. Recent neurobiological studies have provided evidence for the neuroprotective effects of opioids [1,9]. A partial reversal of these effects using opioid antagonists indicated that, in addition to specific opioid receptor involvement, non-receptor effects should also be examined.…”
Section: Introductionmentioning
confidence: 98%
“…Since past investigations have reported biphalin to play a central role in reducing neuronal cellular edema by modulating ion transporter function and expression (Yang et al, 2011a), and reduce edema in both hippocampal slices subjected to OGD and reduce cellular edema in primary neurons subjected to OGD (Yang et al, 2011b), the first aim of this study was to detect the anti-edematous efficacy of biphalin in vivo and compare it to classical, OR-selective agonists. In addition, we compared the effects of these drugs on infarction size and neurological deficit after stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, extensive motor training following stroke increases neuroprotective isoforms of PKC in a time-dependent manner leading to decreased BBB permeability [15]. Likewise δ opioid agonists increase the translocation of the neuroprotective isoform PKC ε from the cytosol to nuclear membrane following stroke, thus providing protection for neurons [16]. …”
Section: Introductionmentioning
confidence: 99%